ENVIRONMENT EFFECT IN SELF-REGULATED LEARNING - Fernando Saragih (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2020)
This study aims at finding and analyzing the influence of parenting style and peer group toward the self regulated learning. These goals are considerably based on the lack of student learning independence occurred during the learning process at school. The theory used in this research is the social cognitive of self regulation. This theory explains that the learning independence is formed by individual, behavior, and the environment.  This is a quantitative research using an explanatory survey method with the questionnaires as the technique of data collection. They consisted of 32 statements which had been evaluated and were valid and reliable to be tested on the respondents. The simple random sampling was applied in order to choose 120 high school students in Purwakarta. All the data were then analyzed by applying the multiple regressions using SPSS. The result of this research shows that there is a positive and a significant effect between the parenting parents and peer group toward the student learning independence. Therefore, parents should adjust the parenting model to the children’s condition as well as implement the values and the basic principles in addition, the role of peer groups is also needed to develop basic values and provide motivation to become more independent figures.Keywords: self regulated learning, Character building, parenting style, peer group, social interactions